Left Anterior Mini-Incision for Pulmonary Valve Replacement Following Tetralogy of Fallot Repair. Issue 2 (March 2020) - Nellis, Joseph R.; Vekstein, Andrew M.; Meza, James M.; Andersen, Nicholas D.; Haney, John C.; Turek, Joseph W.
Pulmonary insufficiency is a known complication following Tetralogy of Fallot repair. With over 90% of patients now surviving to adulthood, surgeons are once again faced with the question of when, and more importantly, how to reintervene. We developed a novel approach to pulmonary valve replacement in this population through a 5-cm left anterior mini-incision. The incision is optimized for exposing and operating on the right ventricular outflow tract and the main pulmonary artery in patients with a history of median sternotomy. Early outcomes are reassuring, and we believe our approach is a safe and reliable alternative to median sternotomy within this patient population, with the ability to quickly convert intraoperatively when needed.